Acetabular Labral Reconstruction: Development of a Tool to Predict Outcomes. Issue 13 (November 2018) - Lebus, George F.; Briggs, Karen K.; Dornan, Grant J.; McNamara, Shannen; Philippon, Marc J.
Background: Acetabular labral reconstruction has demonstrated good results for labral lesions not amenable to labral repair. Purpose: To determine the predictors of outcomes at a minimum 2 years after labral reconstruction. Study Design: Case series; Level of evidence, 4. Methods: Patients included in the study underwent labral reconstruction with a minimum 2-year follow-up. The primary outcome variable was the Hip Outcome Score–Activities of Daily Living (HOS-ADL). Secondary outcome measures included the 12-item Short Form Health Survey physical component summary (SF-12 PCS) and patient satisfaction with surgical outcomes. Preoperative and intraoperative variables assessed included demographics, prior surgery, chronicity of symptoms, radiographic measurements, preoperative outcome scores, and findings at arthroscopic surgery. Predictors were assessed using logistic regression with restricted cubic splines. Bivariate statistics assessed risk factors for reoperation including revision arthroscopic surgery and total hip arthroplasty (THA). Results: Three hundred seventeen of 368 labral reconstructions were available for follow-up (86.1%). Of these, 42 were converted to THA (13.2%) and 35 required revision arthroscopic surgery after labral reconstruction (11.0%). Factors associated with THA included older age, ≥2 previous surgeries, ≤2 mm of joint space, and lateral center edge angle (LCEA) <25°. Factors associated with revision included female sex, ≥2 previous surgeries, and LCEA <25°. Six patients refused to participate (1.9%), leaving 234 with a minimum follow-up of 2 years (mean, 3.7 years [range, 2.0-11.3 years]). These patients had significant improvement in HOS-ADL (71 to 90; P < .001), HOS-Sport (47 to 75; P < .001), Western Ontario and McMaster Universities Osteoarthritis Index (27 to 9; P < .001), modified Harris Hip Score (65 to 85; P < .001), and SF-12 PCS scores (41.6 to 53.1; P < .001). Median postoperative satisfaction was 9. Predictors of improvement for the HOS-ADL included higher preoperative HOS-ADL scores ( P < .001), joint space >2 mm ( P = .004), and no prior surgery ( P = .039). Predictors of improvement for the SF-12 PCS included higher preoperative SF-12 PCS scores ( P < .001), subacute chronicity (3 months to 1 year) of symptoms ( P = .013), and joint space >2 mm ( P = .046). Joint space >2 mm ( P < .001) and higher preoperative SF-12 scores (PCS: P = .034; mental component summary: P = .039) predicted higher satisfaction. Conclusion: At a minimum 2 years' follow-up, patients who did not undergo conversion to THA (13.2%) or require revision (11.0%), reported significant improvement in outcome scores and high satisfaction with outcomes. Predictors of revision or THA included ≥2 previous surgeries, low LCEA, female sex for revision, and narrowed joint space for THA. Higher preoperative outcome scores were the most significant predictors of improvement after labral reconstruction. Lower preoperative scores, joint space narrowing, and history of surgery were predictive of an inferior result and decreased postoperative satisfaction.